2020
DOI: 10.1159/000506930
|View full text |Cite
|
Sign up to set email alerts
|

Endocytoscopic Observation of Non-Ampullary Mucosal Duodenal Cancer

Abstract: KeywordsEndocytoscopy system · Non-ampullary duodenal epithelial tumor · Duodenal cancer · Mucin phenotype Abstract Our previous study of duodenal adenoma using an endocytoscopy system (ECS) demonstrated that disappearance of goblet cells and spindle-shaped nuclei with loss of polarity were characteristic features. In addition, round duct openings and finger-like projections were observed in tubular adenoma and villous adenoma, respectively. Here, we retrospectively investigated six cases of histologically pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The use of ECS adds additional cellular information in real time to the findings of NBI magnification endoscopy in vivo. We previously reported that "enlarged oval-shaped nuclei" are a characteristic feature of duodenal cancer when using the maximum magnification power of the ECS 12 . In the present study, enlarged oval nuclei were confirmed in all of the duodenal cancer lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ECS adds additional cellular information in real time to the findings of NBI magnification endoscopy in vivo. We previously reported that "enlarged oval-shaped nuclei" are a characteristic feature of duodenal cancer when using the maximum magnification power of the ECS 12 . In the present study, enlarged oval nuclei were confirmed in all of the duodenal cancer lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The endocytoscopy system (ECS) is a novel ultra-high-magnification endoscope that can visualize surface epithelial cells 10 . We have previously reported the features of normal duodenal mucosa, duodenal adenoma and non-ampullary mucosal duodenal cancer revealed by ECS 11,12 . Nuclei in normal duodenal mucosa were found to show a regular arrangement in each villus and goblet cells were sparse, whereas adenomatous lesions showed loss of goblet cells and spindle-shaped nuclei with loss of polarity.…”
mentioning
confidence: 99%
“…37 Concerning duodenal cancer, few articles have reported the ECS features of nonampullary duodenal cancer. 37À39 Also, the ECS features of NAMDC, with reference to conventional histology combined with the mucin phenotype, were evaluated by the same group 40 who showed that oval-shaped nuclei and nuclear enlargement were the primary characteristics of this cancer.…”
Section: Small Bowelmentioning
confidence: 99%
“…4 We have previously reported that enlarged oval-shaped nuclei are a feature of duodenal cancer that can be visualized using endocytoscopy. 5 A 28-year-old woman with PJS underwent upper gastrointestinal endoscopy for periodic surveillance of gastrointestinal neoplasms. PJS was diagnosed on the basis of typical mucocutaneous pigmentation and PJ polyps in the jejunum and colon.…”
Section: Mucosal Duodenal Cancer Originating From a Peutz-jeghers Polyp: Endocytoscopic Featuresmentioning
confidence: 99%
“…The present study corroborates previous findings to maintain that CH-EUS should always be combined to EUS-tissue sampling and CT to obtain as much information as possible in PanNENs patients. 5 Authors declare no conflict of interest for this article.…”
mentioning
confidence: 99%